Emotional Intelligence Competencies Developed Through Raja Yoga Meditation: A Study of Women in National Capital Region of India - Rohatgi, Prachi; Singh, Dr. Manju (The journal of contemporary issues in business and government, 2021)
Brahma Kumaris Sahaj Raja Yoga Meditation is a simple yet practical techniqueto bring the mental peace and inner harmony in today’s chaotic times. The research on the practices of such techniques has shown that, they are great help in thestress management and in the prevention of many of the psychosomaticdiseases. Raj Yoga is the highest yoga that empowers the self to rule the mind, sense-organs and the body. It is based on the Prajapati Brahma Kumarie’s school of thought. There are several psychological benefits incurred by Raja yoga which have not been highlighted due to scarcity of scientific studies.The present study examined the effect of Raja Yoga Meditation practice on emotional intelligence of women who’s emotional and behavioural responses varied on the basis of Biopsychosocial factors. Especially in Indian society women’s mental health is affected mainly due to male chauvinism culture.A large no of women population is still not open for their emotional expression which is not a true definition of ‘women empowerment’ in contemporary times. Mere legislative governance will not help in this, women need to feel freedom at core level. The paper is based on primary data collected through field survey of 600 women from NCR region of India Results suggest that the group practicing Raja Yoga had significantly less emotional disturbance and able to manage their emotions well in comparison to the group not practicing Raja Yoga Meditation.